2020
DOI: 10.3390/molecules25225395
|View full text |Cite
|
Sign up to set email alerts
|

Betacyanins and Betaxanthins in Cultivated Varieties of Beta vulgaris L. Compared to Weed Beets

Abstract: There are 11 different varieties of Beta vulgaris L. that are used in the food industry, including sugar beets, beetroots, Swiss chard, and fodder beets. The typical red coloration of their tissues is caused by the indole-derived glycosides known as betalains that were analyzed in hypocotyl extracts by UV/Vis spectrophotometry to determine the content of betacyanins (betanin) and of betaxanthins (vulgaxanthin I) as constituents of the total betalain content. Fields of beet crops use to be also infested by wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 56 publications
1
18
1
2
Order By: Relevance
“…Interestingly, Smeriglio et al [ 22 ] found the highest ORAC values (oxygen scavenging activity) in orange cactus pear fruit. It was reported by Skalicky et al [ 9 ] that the red pigment constituent showed a better correlation with antioxidant activity. Koss-Mikolajzyk et al [ 23 ] reported that the antioxidant activity of betalains decreased in the following order: orange Opuntia > red Opuntia > yellow Opuntia.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, Smeriglio et al [ 22 ] found the highest ORAC values (oxygen scavenging activity) in orange cactus pear fruit. It was reported by Skalicky et al [ 9 ] that the red pigment constituent showed a better correlation with antioxidant activity. Koss-Mikolajzyk et al [ 23 ] reported that the antioxidant activity of betalains decreased in the following order: orange Opuntia > red Opuntia > yellow Opuntia.…”
Section: Resultsmentioning
confidence: 95%
“…‘Betalains’ are divided into two main structural groups: the red to red-violet betacyanins (Bc) and the yellow-orange betaxanthins (Bx). With new methods and technologies, 180 different betacyanin pigments have already been described [ 9 ]. These are secondary metabolites that derive from l -tyrosine (polar aromatic amino acid) via the formation of l -dihydroxyphenylalanine ( l -DOPA).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the study of Sharma et al [39], BX was mentioned as more strongly temperature-dependent concerning BC. Skalicky and coworkers [40] claimed that the absolute stability of betalains was during storage at 22 °C for 6 h. In the study of degradation of betalains in milk, temperature elevation (10 °C) induced an approximately 1.5-fold higher reaction rate [16]. At any specific temperature, somehow, the asymptotic degradation of the color occurred after a certain time of heat treatment [19].…”
Section: Stability Of Betalain Compoundsmentioning
confidence: 99%
“…The beets that were used for these measures were from an unknown cultivar (purchased in a supermarket), but had the typical color of normal beetroots. It is nevertheless possible that other red beet cultivars may have higher betanin content, as betalain concentrations have been reported to vary from 97 mg of betacyanins/100 ml to 500 mg betanin/kg of fresh weight ( Lee et al, 2014 ; Skalicky et al, 2020 ). By coexpression of ADHα with the three other genes, the amount of betanin reached 2.3–2.7 g/kg of fresh weight, about 4 times the amount found in the red beet control.…”
Section: Discussionmentioning
confidence: 99%